Acute Toxicity of NH4Cl to Tambra Fish (Tor Tambroides) Fry - Gunawan Pratama Yoga; Kristin Noni Riyanti Buraen; Sutanto Sutanto (Indonesian Society of Limnology, 2021)
Ammonia is one of the nutrient wastes products which can be toxic to all vertebrates, including fish. Usually, ammonia toxicity is expressed as Total Ammonia Nitrogen (TAN, mgN/L). Tambra fish (Tor tambroides) is freshwater fish with important economic value in some areas in Indonesia. According to overfishing and forest degradation, the fish has become threatened. This research aimed to calculate the LC50 value of ammonia to Tambra fish (Tor tambroides) and estimate NOEC, LOEC, and MATC values of ammonia to Tambra fish (Tor tambroides). This study was conducted using the static test method with two steps. The first stage is a preliminary test, where the preliminary test is observed for 24 hours With five concentrations excluding control. Whereas in the second stage that is carried out, observation for 96 hours with four concentrations excluding control. The Probit test is Performed to obtain LC50 value results, then proceed with ammonia analysis using the Salicylate Test Kit method. The results showed that ammonia had acute toxicity with LC50-96 hour value of NH4Cl against Tambra fish fry (Tor tambroides) in the amount of 354.615 mg/L. Ammonia caused acute toxicity to Tambra fish fry (Tor tambroides).The LC50-96 hour value was 354.615 mg/L in the form of Total Ammonia Nitrogen (TAN) or it was equivalent to un-ionized Ammonia (NH3) of 9.8937 mg/L, while values of the Lowest Observed Effect Concentration (LOEC) and No Observed Effect Concentration (NOEC) of ammonia on Tambra fish (Tor tambroides) were 578.24 mg/L and 280.18 mg/L, respectively.